2019
DOI: 10.1136/bmjdrc-2019-000787
|View full text |Cite
|
Sign up to set email alerts
|

Adverse differences in cardiometabolic risk factor levels between individuals with pre-diabetes and normal glucose metabolism are more pronounced in women than in men: the Maastricht Study

Abstract: ObjectiveTo investigate whether adverse differences in levels of cardiovascular risk factors in women than men, already established when comparing individuals with and without diabetes, are also present before type 2 diabetes onset.Research design and methodsIn a population-based cohort study of individuals aged 40-75 years (n=3410; 49% women, 29% type 2 diabetes (oversampled by design)), we estimated associations with cardiometabolic and lifestyle risk factors of (1) pre-diabetes and type 2 diabetes (referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
1
16
0
1
Order By: Relevance
“…However, there are some plausible candidates that may explain this phenomenon. Several prior investigations have demonstrated that the differences in cardiovascular risk factors associated with deterioration of glucose tolerance are greater in women than men [ 9 11 , 40 , 41 ]. Accordingly, we found that prediabetic and newly diagnosed T2DM women exhibited greater relative differences in BMI, waist circumference, blood pressure, and HOMA-IR than prediabetic and men with newly diagnosed T2DM when compared with their NGT counterparts with formal tests for glucose tolerance status × sex interaction being statistically significant (Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some plausible candidates that may explain this phenomenon. Several prior investigations have demonstrated that the differences in cardiovascular risk factors associated with deterioration of glucose tolerance are greater in women than men [ 9 11 , 40 , 41 ]. Accordingly, we found that prediabetic and newly diagnosed T2DM women exhibited greater relative differences in BMI, waist circumference, blood pressure, and HOMA-IR than prediabetic and men with newly diagnosed T2DM when compared with their NGT counterparts with formal tests for glucose tolerance status × sex interaction being statistically significant (Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…40 This time window may offer clinicians the opportunity to identify those at increased risk for diabetes and subsequently offer the opportunity for timely intervention. 31 As cardiovascular risk factor levels seem to deteriorate more strongly in women than in men, before the onset of diabetes, 16 it is of great importance to conduct a thorough cardiovascular risk assessment in women at risk of diabetes and those with overt diabetes, while not neglecting men. 31 Moreover, increasing awareness among physicians about the stronger deterioration of risk factors in women is Epidemiology/Health services research recommended to prevent women with diabetes from being treated less aggressively than men.…”
Section: Discussionmentioning
confidence: 99%
“… 9 The reasons for these sex differences are likely multifactorial, for example physiological differences between women and men, including the impact of sex hormones, 10–12 female-specific factors such as age of menarche, menopause, and childbearing history, oral contraception, and hormone replacement therapy 13–15 and a more adverse cardiometabolic risk profile among women than men with T2D. 16 17 In addition, healthcare provision for the prevention and delay of cardiovascular complications between men and women with diabetes may differ. 13 15 17–21 …”
Section: Introductionmentioning
confidence: 99%
“…In future studies, it would be useful to investigate possible sex differences in cardiovascular risk factor levels associated with glucose metabolism status and across levels of glycemic control. Previous results from our research group indicated that there are already sex differences in cardiometabolic risk factors to women's disadvantage before the development of type 2 diabetes, albeit weaker than in type 2 diabetes, with greater differences in systolic blood pressure and lipid levels among women than men with prediabetes and across levels of HbA1c [43]. To further understand the effects of sex differences in adiposity, detailed body composition and body fat distribution measurements conducted by DEXA and MRI can be used.…”
Section: Future Perspectivementioning
confidence: 99%